ANALISIS PENGARUH ACHIEVMENT, INOVASI TERHADAP KINERJA ENTREPRENEUR UKM PENGRAJIN HOME INDUSTRI BATIK DENGAN PERSONAL CONTROL SEBAGAI VARIABEL MODERATING DI SURAKARTA - Y. Djoko Suseno & Alwi Suddin (Universitas Slamet Riyadi, 2019)
This study aims to determine the significant effect between I) Achievment on the performance of Employee, 2) Inovation on Employee Performance, 3) Personal Control on the Performance, 4) Achievment on employee Performance is moderated by Personal Control, and 5) Inovastion on Employee Performance is moderated by the Personal Control in the UKM Batik SurakartaThe population in the in this study werw ccoper Batik in the district of Surakarta numbering 60 cooper batik . The sampling technique used in this research is Propotional Smpling. Techiques of data collection using questionares, observation anda domumentation. Analysis using multi linier regression using a moderating variable.The result obtained by dat analysis 1) Quesionaire study variables consisted of variables Achievment , Inovation, Personal Control and Performance of all valid and reliable. Classic assumption test result showed that multiple linier regression yielded escaped the problems of classical assumptions.The result of data analysis also showed that 1) Achievment was significantly positively affect the performance of employee,,2) Inovastion positively significantly affect the performance of employee , 3) Personal Control also positive significantly affect the performance of employee Handicraf batik, 4) Personal Control positive significantly moderate the effect of Achievment on employee performance handicraft batik, 5) Personal Control was also positive significantly moderat the effect of the work Inovasion on employee Performance Handicraft Batik.Result of analysis R2 value obtained for 0,243 %, it shows tahat the Employee Performance handicraft is influenced by achievement, Inovastion, and Personal Control and is 24,3 % while the remaining 75,7 % who are influenced by other variaveble examined in the study.